PEMETAAN KESELARASAN INDIKATOR TUJUAN PEMBANGUNAN BERKELANJUTAN /SUSTAINABLE DEVELOPMENT GOALS (TPB/SDGs) PADA RENCANA PEMBANGUNAN KABUPATEN INDRAGIRI HILIR - Roberta Zulfhi Surya (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
This SDGs Data Mapping exercise helps us to estimate readiness of Indragiri Hilir in applying proposed SDGs indicators to measure SDGs targets; for which indicator data improvement is required and where the data gaps exist. SDGs consist of 17 goals, 169 targets and 241 Indicators. In order to be able to measure the achievements of the SDGs targets, set of indicators are required and data needs to be available to apply those indicators. The exercise was conducted through desk review method by mapping for each SDGs Target existing relevant indicators used or proposed in the local documents: Indragiri Hilir Medium- Term Development Plan 2013-2018 (RPJMD) and others relevant documents as required. The indicators mapping then followed by data mapping for each indicator based on the availabity and quality of data from Statistics Agency (BPS) and line Agencies. The indicators mapping showed 16 goals, 46 targets dan 67 Indicators relevant.